Promiscuous enzyme-catalyzed cascade reaction in water: Synthesis of dicoumarol derivatives. Issue 10 (15th May 2019) - Fu, Yajie; Lu, Zeping; Fang, Ke; He, Xinyi; Huang, He; Hu, Yi
Graphical abstract: Highlights: We have demonstrated an efficient enzymatic method for the synthesis of dicoumarol derivatives. The use of green solvent, mild reaction conditions, recyclable biocatalyst, generality high yields and environmental friendliness are the important attributes of the present protocol. Abstract: Lipase RMIM was firstly used as a promiscuous biocatalyst to catalyze the Knoevenagel-Michael cascade reactions of 4-hydroxycoumarin with aromatic, heterocyclic or aliphatic aldehydes to synthesize dicoumarol derivatives in water. Results showed that the adopted methodology could offer many advantages, such as mild reaction conditions, pure aqueous reaction system, wide substrate applicability, recyclable catalyst, excellent yields (81–98%), operational simplicity, and environmentally friendly reactions.